Technology and equipment of roll straightening of sheet metal - V. A. Tamila; I. I. Vegera; V. V. Liaukovich; A. V. Vetoshkin (Литьë и металлургия)
The features of the editing technology, possible defects of sheet metal and piece blanks of complex configuration are presented. The main schemes and designs of sheet‑straightening machines are considered, as well as the main directions of improvement of LSM designs and editing technologies are highlighted. The analysis of the process of roll straightening is presented taking into account the phenomena occurring in a metal undergoing alternating loading with decreasing amplitude (interaction of elastic and plastic deformation, Bauschinger effect, etc.). The parabolic dependence of the residual curvature on the yield strength is noted. The obtained data were used in the design of the roll straightening complex and the technology of straightening sheet blanks of complex configuration.